Analysis of cause-effect relationship of hip dysplasia in pre-school children - Anna Rudenko; Oleksandr Zviriaka (Kharkiv State Academy of Physical Culture, 2015)
Purpose: to analyze and scientifically substantiate peculiarities of cause-effect relationship of hip dysplasia in pre-school children. Material and Methods: analysis and systematization of scientific and methodological literature, medical histories, anamneses, interviews and questionings. Results: it is specified that failure to timely identify and eliminate the symptoms of hip dysplasia in pre-school children leads to negative consequences, namely limited amplitude of hip joint movements; lower limp muscle weakness; valgus and varus deformations of lower limp; increasing of L-lordosis; skewness of hip bones; scoliosis; claudication. Conclusions: the modern state of the problem of hip dysplasia in pre-school children is analyzed. The cause-effect relationship is defined, their mutual transition is projected. All cause-effect relationships are in direct proportion and in constant interaction: the cause the forms effect and the effect influences the cause